Optical and chemical properties and oxidative potential of aqueous-phase products from OH and 3C∗-initiated photooxidation of eugenol - X. Li; Y. Tao; L. Zhu; S. Ma; S. Luo; Z. Zhao; N. Sun; X. Ge; Z. Ye (Atmospheric Chemistry and Physics, 2022)
Aqueous reactions may turn precursors into light-absorbing and toxic products, leading to air quality deterioration and adverse health effects. In this study, we comprehensively investigated eugenol photooxidation (a representative biomass-burning-emitted, highly substituted phenolic compound) in the bulk aqueous phase with direct photolysis, a hydroxyl radical (OH), and an organic triplet excited state (3C∗). Results show that the degradation rates of eugenol followed the order of 3C∗><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="16pt" height="11pt" class="svg-formula" dspmath="mathimg" md5hash="815d137e7297c0cca1ef78cd8c40eec9"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-22-7793-2022-ie00001.svg" width="16pt" height="11pt" src="acp-22-7793-2022-ie00001.png"/></svg:svg> OH > direct photolysis. During the 3C∗-initiated oxidation, different reactive oxygen species (ROS), including 3C∗, OH, 1O2, and O<msubsup>2⚫-</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="12pt" height="16pt" class="svg-formula" dspmath="mathimg" md5hash="38e88279edae3c2306125c2b688c882b"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-22-7793-2022-ie00002.svg" width="12pt" height="16pt" src="acp-22-7793-2022-ie00002.png"/></svg:svg>, can participate in the oxidation of eugenol, quenching experiments verified 3C∗ was the most important one, while, during OH-initiated oxidation, O<msubsup>2⚫-</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="12pt" height="16pt" class="svg-formula" dspmath="mathimg" md5hash="ac414ce3e6bd5a189a6b4ffc7d500671"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-22-7793-2022-ie00003.svg" width="12pt" height="16pt" src="acp-22-7793-2022-ie00003.png"/></svg:svg> was a more important ROS than OH for degrading eugenol. The rate constants under saturated O2, air, and N2 followed the order of kO2>kAir>kN2<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="75pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="3c87aa62b339ba385bbeda678b23bbcc"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-22-7793-2022-ie00004.svg" width="75pt" height="14pt" src="acp-22-7793-2022-ie00004.png"/></svg:svg> for both direct photolysis and OH-initiated oxidation but changed to kAir>kN2>kO2<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="75pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="c84023e2cd563129390548879665eb10"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-22-7793-2022-ie00005.svg" width="75pt" height="14pt" src="acp-22-7793-2022-ie00005.png"/></svg:svg> for 3C∗-mediated oxidation. pH and dissolved oxygen (DO) levels both decreased during oxidation, indicating the formation of acids and the participation of DO in oxidation. Ultraviolet and visible (UV-vis) light absorption spectra of the reaction products showed a clear absorbance enhancement in the 300–400 nm range for all three sets of experiments, and new fluorescence at excitation/emission =250/<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="37pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="7612daa1a6f4a9018aa6db874eb7bd2e"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-22-7793-2022-ie00006.svg" width="37pt" height="14pt" src="acp-22-7793-2022-ie00006.png"/></svg:svg> (400–500) nm appeared, suggesting the formation of new chromophores and fluorophores (brown carbon species). These species were likely attributed to humic-like substances (HULIS), as shown by the increases in HULIS concentrations during oxidation. Large mass yields of products (140 %–197 %) after 23 h of illumination were obtained, and high oxidation degrees of these products were also observed. Correspondingly, a series of oxygenated compounds were identified, and a detailed reaction mechanism with functionalization as a dominant pathway was proposed. At last, the dithiothreitol (DTT) assay was applied to assess the oxidation potential of the reaction products, and the end products of all three sets of experiments showed higher DTT consumption rates than those of eugenol, indicating that more toxic species were produced upon aqueous oxidation. Overall, our results from using eugenol as a model compound, underscore the potential importance of the aqueous processing of biomass burning emissions in secondary organic aerosol (SOA) formation.